ANALYTICAL ASSESSMENT ON THE ACHIEVEMENTS AND FAILURES OF MALAYSIAN VISION 2020: SOME MANAGEMENT POLICY GUIDANCE FOR BRUNEI VISION 2035 - Razali bin Mat Zin; Faizuddin bin Mahfuzh; Hajah Nur Annisa binti Haji Sarbini (University of Islam Malang, 2021)
2020 is a Malaysian ideal introduced by the former Prime Minister of Malaysia Dato Seri Dr. Mahathir bin Mohamad when tabling the Sixth Malaysia Plan in 1991. The vision calls for the nation to achieve a self-sufficient industrialized nation in the year 2020, encompasses all aspects of life, from economic prosperity, social well-being, world class educational, political stability, as well as psychological balance. His Majesty Sultan Haji Hassanal Bolkiah Mu'izzaddin Waddaulah, Sultan and Yang Di-Pertuan Negara Brunei Darussalam consented to this long-term vision, which is known as the Brunei Vision 2035. This vision aspires that by 2035, Brunei Darussalam develops into a nation which will be widely recognized for the accomplishment of its educated and highly skilled people measured by the highest international standards; quality of life that is among the Top 10 nations in the world and a dynamic and sustainable economy with income per capita within the Top 10 countries in the world. This paper critically analyzed the achievements and failures of Malaysian Vision 2020 in order to extract some meaningful lessons for Brunei policy makers in managing its Brunei Vision 2035.